Bioactive compounds from marine macroalgae and their hypoglycemic benefits. (February 2018) - Zhao, Chao; Yang, Chengfeng; Liu, Bin; Lin, Luan; Sarker, Satyajit D.; Nahar, Lutfun; Yu, Hua; Cao, Hui; Xiao, Jianbo
Abstract: Diabetes mellitus is a group of chronic metabolic disorders characterized by hyperglycemia due to defects in insulin action and/or secretion. It is a worldwide problem which has led to illness and premature mortality for many people, and the number of diabetes cases has been rising sharply. Unluckily, many conventional antidiabetic agents either show limited efficacy or serious mechanism-based side effects. Marine macroalgae possess tremendous nutritional value and have been well-known to cure and prevent diabetes. An increased interest in various bioactive natural products from marine macroalgae, as a potential source of effective antidiabetic agents, has been observed in recent years. The effects of macroalgae may delay the development of diabetes and alter the metabolic abnormalities through various mechanisms of actions. This review provides an overview of marine macroalgae used to prevent and manage diabetes and explores the hypoglycemic properties of macroalgae-derived bioactive compounds such as polyphenol, bromophenols, sulfated polysaccharides, fucoidan, fucosterol, phlorotannins, carotenoid pigments and fucoxanthin with their probable mechanisms behind hypoglycemic activity. Highlights: Aacroalgae and macroalgae-derived bioactive compounds as anti-diabetic agents. The mechanisms of marine macroalgae for diabetes. Clinical studies are necessary to confirm marine macroalgae as anti-diabetic agents.